Effectiveness of Bone Marrow–Derived Platelet-Rich Fibrin on Rotator Cuff Healing in a Rabbit Degenerative Model. Issue 12 (October 2022) - Uno, Tomohiro; Maruyama, Masahiro; Satake, Hiroshi; Takakubo, Yuya; Toyono, Shuji; Xing, Liu; Huang, Hanqing; Yuki, Issei; Suzuki, Akemi; Mura, Nariyuki; Takagi, Michiaki
Background: Platelet-rich fibrin (PRF) is a second-generation platelet concentrate. Although peripheral blood–derived PRF (P-PRF) is commonly applied in biological augmentation, there is no report about the therapeutic effect of bone marrow–derived PRF (BM-PRF) for degenerative rotator cuff tears (RCTs). Purpose/Hypothesis: To examine the effects of platelet-rich plasma (PRP), P-PRF, and BM-PRF during rotator cuff repair (RCR) in degenerative RCTs in rabbits. We hypothesized that BM-PRF would accelerate the bone-tendon healing after RCR. Study Design: Controlled laboratory study. Methods: Degenerative RCT models were created 2 weeks before beginning the study, and 68 juvenile rabbits were divided into 4 groups: the control, PRP, P-PRF, and BM-PRF groups. RCR without augmentation was done in the control group. PRP was prepared by centrifuging peripheral blood twice using a plastic tube. P-PRF and BM-PRF were prepared by centrifuging peripheral blood and bone marrow, respectively, using a glass tube. Rabbits from PRP, P-PRF, and BM-PRF groups were administered the augmentation in a similar fashion for RCR, between the rotator cuff and the footprint of the humerus. At 4, 8, and 12 weeks, rabbits were euthanized and histologically assessed using hematoxylin and eosin staining, Alcian blue staining, and immunohistochemical staining for type I and III collagen. The sections were also evaluated with immunofluorescence staining of vascular endothelial growth factor (VEGF) at 4 weeks. Results: The continuity was significantly better in the BM-PRF group at 4 weeks ( P < .05). Immunofluorescence staining demonstrated that VEGF-positive stained cells were significantly greater in the BM-PRF group than in the control group ( P < .01). The modified tendon maturing score was significantly greater in the BM-PRF group than in the control and PRP groups at 12 weeks ( P < .05). There was no significant difference in the modified tendon maturing score of the P-PRF group compared with the control group. Conclusion: The rabbit model of degenerative RCTs demonstrated that RCR combined with BM-PRF enhanced tendon-bone continuity and increased the VEGF-positive cells at 4 weeks and obtained preferable tendon-bone maturation at 12 weeks. Clinical Relevance: RCR augmented with BM-PRF has the potential to improve clinical outcomes for RCTs.